1984
DOI: 10.1021/ic00187a007
|View full text |Cite
|
Sign up to set email alerts
|

Ferric isoporphyrins from hydroperoxide oxidation of (tetraphenylporphinato)iron(III) complexes

Abstract: Reaction of chloro[tetrakis(4-methoxyphenyl)porphinato]iron(III) with Zert-butyl hydroperoxide yields an isoporphyrin, hydroxo-or 10,15,-5/f,21/f-porphinato]iron(III), isolated as a microcrystalline solid. This compound is of interest as an example of an isoporphyrin generated by chemical rather than electrochemical oxidation and because it represents an alternative to the oxoiron species currently presumed to be involved in biomimetric oxidations utilizing peroxy acids and hydroperoxides mediated by (meso-tet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 2 publications
(3 reference statements)
0
13
0
2
Order By: Relevance
“…Gold and co-workers first reported the synthesis of an iron isoporphyrin, [5-(tert-butylperoxy)-5,10,15,20-tetrakis(4-methoxyphenyl)-5H,21Hporphinato]iron(III), (6) by the reaction of [Fe(4-OCH 3 -TPP)Cl] with tert-butyl hydroperoxide. 23 Observing the formation of isoporphyrin as the reaction product of iron porphyrin, [Fe(4-OMe-TPP)Cl] with excess tert-butyl hydroperoxide oxidant, author suggested that biomimetic oxidations of heme proteins may proceed via a peroxy-isoporphyrin intermediate rather than the high-valent iron(IV)-oxo species. They characterized the iron-isoporphyrin using electronic, 1 H NMR and mass spectrometry.…”
Section: Iron Isoporphyrinmentioning
confidence: 99%
See 2 more Smart Citations
“…Gold and co-workers first reported the synthesis of an iron isoporphyrin, [5-(tert-butylperoxy)-5,10,15,20-tetrakis(4-methoxyphenyl)-5H,21Hporphinato]iron(III), (6) by the reaction of [Fe(4-OCH 3 -TPP)Cl] with tert-butyl hydroperoxide. 23 Observing the formation of isoporphyrin as the reaction product of iron porphyrin, [Fe(4-OMe-TPP)Cl] with excess tert-butyl hydroperoxide oxidant, author suggested that biomimetic oxidations of heme proteins may proceed via a peroxy-isoporphyrin intermediate rather than the high-valent iron(IV)-oxo species. They characterized the iron-isoporphyrin using electronic, 1 H NMR and mass spectrometry.…”
Section: Iron Isoporphyrinmentioning
confidence: 99%
“…Paramagnetic isoporphyrins like iron isoporphyrin show a similar upfield shifting of pyrrole β-H peaks in the 1 H NMR spectrum. 23 Infra-red spectroscopy can be used as a tool for the formation of some isoporphyrin complexes, since a free molecule or a nucleophile has a different vibrational frequency from the same nucleophile that has been covalently bound. There is a report on characterization of the zinc nitrato-isoporphyrin, which showed a strong peak at 1659 cm −1 due to the covalently bound nitrite anion to the meso carbon atom which is different from the free nitrate anion stretching frequency.…”
Section: H Nmr Spectramentioning
confidence: 99%
See 1 more Smart Citation
“…synthesized Zn methoxy‐isoporphyrin from ZnTPP by electrochemical oxidation and followed by the addition of methanol [5] . In the following years, researchers tried to synthesize and isolate stable isoporphyrin complexes but not succeeded due to reconversion into the corresponding porphyrins [6–8] . In 1992, Xie et al.…”
Section: Introductionmentioning
confidence: 99%
“…The existence of this type of compound was first suggested by Woodward [1] in 1961, whose prediction was confirmed about a decade later when Dolphin et al [2] reported the first synthesis of a metalloisoporphyrin ( 4 ) from zinc 5,10,15,20-tetraphenylporphyrin by way of electrochemical oxidation. Other methods for directly generating metallo-isoporphyrins since then include peroxide oxidation [3, 4] and photooxidation [58]. …”
Section: Introductionmentioning
confidence: 99%